Lurik Dan Fungsinya Di Masa Lalu - Sri Wuryani (Ornamen, 2013)
Lurik is one of the traditional textiles ever developed in severalregions in Indonesia, and one of them is in Surakarta. Thereis an opinion that the wordlurik have the same root with the wordÂ lorek in Javanese, meaning lines, and also the word lirik-lirikmeaning striped by small lines.The syllable rik means a line oran imprint of a shallow trench. Javanese people are familiar withthe word mageri which means protecting from things that areevil and invisible . Visually lurik can be divided into two, namelylurik ciut and lurik wiyar In terms of pattern lurik is divided into3, pakan malang, lajuran and cacahan. Lurik in its times not justas a mere body cover, but it has a deeper meaning, a symbolicmeaning concerning with the culture, beliefs and expectations ofthe Javanese people, especially in Surakarta. Kain lurik worn bythe Javanese in ceremonies related to the human life cycle, frombirth to death. Lurik is used in ceremonies associated with beliefsuch as labuhan, adang ceremony etc. But along with the timesthat influence the worldview and human lifestyle, lurik is gettingabandoned . Even if there are still people who use and preserveit itâ€™s only a small number , or already have another function justas for bags, table cloth, chair pads, so its deeper meaning hasbeen neglected.Keywords: Lurik, Fungtion, Symbolic